Consumer protection in microfinance services in mainland Tanzania: A critical analysis of the law - Lukuvi, Mossy (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Award of Degree of Master of Laws (Commercial Law) of Mzumbe University.